The ultimate concept art career guide (3dtotalPublishing, 2017)
"The Ultimate Concept Art Career Guide is an expert-led handbook to help you launch, sustain, and evolve career as an artist in the entertainment industry. With helpful insights and encouragement from experienced freelance artists and leading industry professionals, learn how to create a winning portfolio, develop your online presence, and handle the ups and downs of an art career. Incorporating education and training suggestions, interview tips, and best practice advice, this guide is ideal preparation for anyone wanting to develop a career as a professional concept artist, and artists hoping to explore new career options or considering freelance work." -- Provided by publisher